Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/jnr.25035
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal magnetic resonance imaging quantification of gray matter alterations in relapsing‐remitting multiple sclerosis and neuromyelitis optica spectrum disorder

Abstract: Herein, we combined neurite orientation dispersion and density imaging (NODDI) and synthetic magnetic resonance imaging (SyMRI) to evaluate the spatial distribution and extent of gray matter (GM) microstructural alterations in patients with relapsingremitting multiple sclerosis (RRMS) and neuromyelitis optica spectrum disorder (NMOSD). The NODDI (neurite density index [NDI], orientation dispersion index [ODI], and isotropic volume fraction [ISOVF]) and SyMRI (myelin volume fraction [MVF]) measures were compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 105 publications
1
10
0
Order By: Relevance
“…In addition, similar to the findings of NAWM, two studies explored specific regions of the NAGM 23,27 . Decreased NDI was observed, although mapping in different areas.…”
Section: Resultssupporting
confidence: 58%
See 4 more Smart Citations
“…In addition, similar to the findings of NAWM, two studies explored specific regions of the NAGM 23,27 . Decreased NDI was observed, although mapping in different areas.…”
Section: Resultssupporting
confidence: 58%
“…Decreased NDI was observed, although mapping in different areas. Andica et al, reported GM alterations in the insula, limbic, and paralimbic regions, 23 while Collorone et al observed widespread alterations in the visual cortex, occipital, parietal, and temporal lobes 27 . ISOVF was assessed only in one study, reporting elevated values in extensive NAGM regions, including entorhinal, fusiform, and superior temporal regions, cerebellum cortex, hippocampus, insula, and parahippocampus areas 23 .…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations